Dependent Persons in Spain: estimation of the number and costs for their care - Albarran, Irene (Estudios de Economía, 2016)
This research tries to assess the dependents and Long Term Care costs for nextyears in Spain. To do this, it has been taken account data from the Survey onDisabilities, Impairments and Health Status and population forecasts estimatedby INE, the legal rules passed between 2006 and 2008, and some formerstudies about individual costs of long term care. The key point in this study isthe concept of cost per point of scale. Once calculated, forecasts till 2050 have been estimated. Finally, the results have been compared with those included inthe Long Term Care Act.